The delinquency of 100 recidivists during a period from the age of 18 to 25th-28th year of age (Results of the follow-up studies) (Archives of Criminology, 1965)
In the years 1957/1958 the Department of Criminology of the Polish Academy of Sciences carried out a research in prisons concerning 100 young-adult recidivists aged 17-20. Qualified for the research without any selection were prisoners of tłrat age, convicted by law courts at least twice after the completion of their 17th year of age (regardless of the kind of the offence committed), and serving their term in prison for at least the second time. Their residence in Warsaw or in the environs of Warsaw and their having at least one parent constituted additional criteria. No other information concerning these recidivists was available at the time they were qualified for the research and thus it was not known whether they committed any offences before the completion of their 17th year of age or whether they were tried by the courts at all.At the time of the research in prisons the average age of recidivists was about 20. 50 % of them were convicted twice after the completion of 17 years of age, 25 % were convicted three times and 23 % four times and more. A check in the Juvenile Court revealed. that 80 % of those recidivists underwent trials in Juvenile Courts for thefts as a rule before they completed 17 years of age. Moreover, 11 % of them repeatedly committed thefts as juveniles (under 17) for which they were not tried by the courts. At least 54 % out of 91 recidivists become delinquents under 13 years of age and only 12 % began cornmitting theft at the age of 15 and over. 44 % of recidivists stayed at correctional institutions (as a rule only at a time when they were 15-16 years old).Already during the investigation in prisons in the years 1957/1958, when the average age of recidivists was merely about 20, it was stated that 82 % of them were seriously demoralized. Their subsequent destinies were further investigated in the course of 6 years until the end of 1964. The average age of these 100 recidivists amounted recently to 26 years and six months. Below are presented data relating to their delinquency from the age of 17 to 25-28 years of age. That period comprises 8-11 years, on the average 10 years. 65 % stayed longer in prisons than on liberty, with 36 % staying in prison even longer than two thirds of that entire period. The average period of their staying on liberty between alternate arrests was up to 6 months for 48 % of recidivists, below a year for 80,5 %, and one year and a half and over for 5,4% only. On the average there are 8.3 proved offences for one recidivist (the number of offences for which they were convicted is actually much higher, as not all judicial records could have been examined; the register of the convicted persons does not contain competent information in this respect). Among 830 offences for which 100 recidivists were convicted the offences against property constituted 63 % (among them thefts – 83 %), offences against authonities 16 % (mostly against policemen), offences against the person 13 % and various other offences 8 %. 37 % of recidivists were convicted exclusively for offences against property, and with 27 % the convictions against property outnumbered those against authorities and against the person. 27 % were convicted for various offences with the preponderance of convictions for offences against authorities and against the person. 9 % of recidivists were convicted exclusively for offences against authorities and against the person.The most antisocial offenders, who as a rule since the completion of their 17th year stayed in prison longer than on liberty, for committing thefts for the most part, constitute 50 % among recidivists ąged 25-28. Only 13 % of recidivists can be considered resocialized. Since their last discharge from prison they have remained on liberty for at least 6 years. They work and lead a normal life, they do not abuse of alcohol often. Those 13 recidivists already in their youth displayed the lowest degree of demoralization, most of them were only twice convicted after the completion of 17 years of age and the average number of offences for which they were tried in courts was merely about 4.The inefficacy of imprisonment with regard to young-adult delinquents is dealt with in the final part of this work.During the period of about 10 years after the completion of 17 years of age, the recidivists were jointly sentenced to imprisonment in 466 cases. Imprisonment, not exceeding 6 months time, constituted 31 % of the total, below 1 year – 52 %, below one year and a half – 66 %, below 2 years – 73 % of the total.An analysis of the material shows that penalties inflicted on the now most antisocial recidivists do not differ from those inflicted on recidivists who have not committed any offences at all for the last six years.AIso there is no relationship whatever between the wight of penalty inflicted by the courts and the succession of convictions.The average penalty inflicted does not show any relationship to the rate of recidivism: as regards recidivists convicted three times only, the average penalty amounted to 16 months of prison, for six previous convictions to twelve months, for seven and more convictions - to 13 months of prison. The average penalty is then lower for the recurrent recidivists already convicted six and more times than for the offenders convicted only three times, despite the fact that the most antisocial recidivists, committing thefts for the most part, constitute 83 % of the offenders convicted six times and more.Moreover, the research has shown, that there is no significant relationship between the length of imprisonment and the length of the subsequent stay on liberty before a new arrest. Recidivists discharged after having served a six months term in prison were arrested again before the lapse of half a year in 44 % of cases; recidivists discharged after a term of three and more years, found thernselves in prison again before the lapse of half a year in 63 % of cases.Application of long-term imprisonment does not prevent further recidivism. It is necessary to apply special sanctions during the recidivists' minority and up to 21 years of age with the sole aim of their resocialisation.